Effect of Mycorrhizae on the Growth of Eucalyptus tereticornis Seedlings in Nursery in Different Geo-climatic Conditions - Garg, R. K.; Pandey, A. K.; Goyal, D.; Sharma, R. K. (Indian Forester, 1999)
To identify an efficient mycorrhiza for promoting the growth of Eucalyptus tereticornis in nursery, six species of mycorrhizae [Laccaria fraterna (EM-1083), G. fesciculatum, G. mosseae and three VAM consortia dominated by G. mosseae (G. mosseae 85, G. mosseae 88 and G. mosseae 92)] were screened. The screening procedure involved (i) prior to sowing, mycorrhizae application on elite seeds of E. tereticornis in root trainer cups at three different geographical locations of India namely Patiala (North India), Choudwar (South-East India) and Sewa (Central East India) containing a potting mix; (ii) allowing germination and growth at 32±2°C in root trainer cups, periodic irrigation of seedlings to maintain 30±5% moisture in a greenhouse; and (iii) monitoring the rate of germination, root ramification, shoot biomass and general vigour of the seedlings as a function of mycorrhizal infection, 100 days (from sowing until harvesting/transplantation). It was observed that, in nursery studies vis-a-vis control L. fraterna promoted maximum plant biomass at Patiala and Sewa, while G. mosseae 85 at Choudwar. Mycorrhizal strains affected differently at different sites on the basis of height, chlorophyll, and per cent infection.